THE MAIN ATTRACTION OF CHILDREN TO PHYSICAL ACTIVITY NATIONAL TYPES OF WRESTLING AS THE BASIS - Jumaqulov J. M.; Akhmatov M. S.; Boymatov X. X. (Web of Journals Publishing, 2024)
In this article the issues of mass development of the national type of martial arts - kurash, etc. through an integral national system, as well as their use as a tool of mass involvement of children and students in physical activity are considered.
Keywords: mass sport, national system, kurash, national culture, martial arts, mechanism, children, students.